Disaster management: A Study on knowledge, attitude and practice of emergency nurse and community health nurse - Ahayalimudin, Nurul'Ain; Ismail, Aniza; Mohd Saiboon, Ismail (2012)
Background: Disaster is unpredictable events and the numbers are mounting from day to day. Disaster kills and affects people, demolishes properties and disrupts environment. During disaster, nurses play vital roles in dealing with the victims and it is crucial for nurses to be prepared in facing disaster and aftermath. The aim is to determine knowledge, attitude and practice of emergency nurse and community health nurse towards disaster management. Methods: This comparative cross-sectional study conducted in one states in Malaysia. The data was collected in October and November 2011. The questionnaire distributed to randomly select 468 nurses from emergency departments and health clinics with response rate of 84.6 per cent. Results: There is no difference on knowledge and attitude of both groups where 59.1% are having inadequate knowledge and majority portraying positive attitude. It differs for practice where 56.1% of emergency nurse and merely 30.7% community health nurse are having adequate practice (p<0.001, χ2=24.506). Emergency nurses who involved in disaster response are more likely to have an adequate practice (p<0.01, AOR=4.008, 95% CI=1.691-9.504) and those who attended disaster-related education/training are more likely to have adequate knowledge (p<0.05, AOR=3.807, 95% CI=1.584-9.153) and practice (p=0.001, AOR=4.145, 95% CI=1.804-9.525). Attending disaster-related education/training is predictors to the adequate knowledge (p<0.001, AOR=3.511, 95% CI=2.097-5.881) and practice (p<0.001, AOR=4.080, 95% CI=2.326-7.156), and portraying positive attitude (p<0.05, AOR=2.042, 95% CI=1.025-4.069) among community health nurse. Nurses’ workplace (represent type of nurse) is identified as a predictor to the adequacy of practice (p<0.001, AOR=2.345, 95% CI=1.474-3.730). Conclusion: It has been proven that adequacy of knowledge and practice, and portraying positive attitude is driven by involvement in disaster response and attending disaster-related education. Thus, it is paramount for organization to conduct disaster-related education/training as to improve knowledge and practice towards disaster management. Keywords: disaster management; disaster nursing; emergency nurse; community/public health nurse; knowledge, attitude and practice